Comorbid Conditions in Individuals with Intellectual Disabilities - Matson, Johnny L (Springer, 2015)
This comprehensive edited volume synthesizes the current state of research and practice in psychological, medical, and motor disorders as they affect individuals with intellectual disabilities (ID). It examines how these disorders exist across this population, sometimes confound diagnosis, and often affect individuals’ quality of life. In addition, this book explores which treatments are effective for patients and points to future challenges.